Exploring Ethical and Quality Dimensions of Artificial Intelligence Influence on Trust - Princes, Elfindah; Silalahi, Wilma (Journal of Multidisciplinary Issues, 2025)
Objective – The purpose of this study is to examine how the amount of content generated by artificial intelligence (AI) is affecting the accuracy and reliability of information found online. Methodology – Using a survey-based approach conducted online with a 5-Likert scale, assessed by 10 survey items. Findings – The findings reveal that artificial intelligence does not have a direct effect on trust. Novelty – The conclusion emphasizes the relationship of the variables that may be used to develop a suitable marketing strategy.